TENDENCIES OF DEVELOPMENT OF GLOBAL EDUCATIONAL NETWORKS (FOREIGN EXPERIENCE) - Iryna D. Malytska (Інформаційні технології і засоби навчання, 2010)
In the article the general tendencies of development of global educational networks, use of their resources in education systems of foreign countries are analyzed. The examples of the most popular educational nets are presented.